2022
DOI: 10.1111/ced.15204
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional vitamin D injection for management of keloids

Abstract: chlorpheniramine (2 days after favipiravir therapy ceased), without post-inflammatory hyperpigmentation, but there was some skin exfoliation.Our case is further confirmation that favipiravir can cause skin rash, and a specific allergy test is usually required for diagnosis. Such rashes pose a clinical challenge during favipiravir therapy for COVID-19, as such rashes can be due to the virus itself or to the medication prescribed to treat it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In clinic, 1,25(OH) 2 D3, an active form of vitamin D, inhibits the proliferation of KD fibroblasts, and there are correlations between vitamin D receptor polymorphism and KD formation. Thus, vitamin D may exert an antifibrotic effect partially mediated by matrix MMPs [173]. A highly significant reduction in VSS score was observed after treatment with intralesional vitamin D injection (200,000 IU/1 cm lesion, weekly, 3-4 sessions) in patients with KD [170].…”
Section: Vitamin Dmentioning
confidence: 98%
See 1 more Smart Citation
“…In clinic, 1,25(OH) 2 D3, an active form of vitamin D, inhibits the proliferation of KD fibroblasts, and there are correlations between vitamin D receptor polymorphism and KD formation. Thus, vitamin D may exert an antifibrotic effect partially mediated by matrix MMPs [173]. A highly significant reduction in VSS score was observed after treatment with intralesional vitamin D injection (200,000 IU/1 cm lesion, weekly, 3-4 sessions) in patients with KD [170].…”
Section: Vitamin Dmentioning
confidence: 98%
“…Vitamin A significantly reduces fibroblast proliferation and collagen synthesis in vitro and in vivo [158]. Vitamin D3 slows the progression of tissue fibrosis by KD fibroblasts and inhibits collagen synthesis in dermal fibrosis [170,173]. Vitamin E supplementation is beneficial for wound repair and immune functions [176].…”
Section: Fat-soluble Vitaminmentioning
confidence: 99%
“…A growing body of research in recent years has demonstrated that vitamin D is closely associated with keloid development and progression. For example, vitamin D deficiency could contribute to keloid development, and injection therapy with vitamin D can significantly decrease keloid thickness (81); vitamin D plays an important role in the inhibition of inflammation and fibrosis, which are two inevitable steps in keloid development and progression (82,83); vitamin D plays an important role in the inhibition of inflammation and fibrosis, which are two inevitable steps in keloid development and progression. Some studies have also found lower levels of the vitamin D receptor (VDR) in keloids compared to normal skin, suggesting that VDR may play a role in keloid pathology (84).…”
Section: Vitamin Dmentioning
confidence: 99%